2003
DOI: 10.1182/blood-2002-10-3000
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma tumor progression in the 5T2MM murine model is a multistage and dynamic process of differentiation, proliferation, invasion, and apoptosis

Abstract: IntroductionMultiple myeloma (MM) is still an incurable plasma cell cancer, predominantly localized in the bone marrow (BM). Our group demonstrated that the in vivo homing of these malignant cells to the BM is a selective process of directed migration and selective survival in this organ. 1 Once the cells have entered the BM, they have an intensive cross-talk with the BM stromal cells and induce a microenvironment that supports their survival and growth. 2 At time of diagnosis, MM is already a well-established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 37 publications
4
36
1
Order By: Relevance
“…To our knowledge, this is the first report demonstrating the potential of isolated primary CD138-enriched PCs to proliferate, propagate, and produce typical myeloma manifestations in vivo. These results are in contrast to recent study showing the inability of purified CD138-expressing PCs to grow in NOD/SCID mice, 8 but in accord with previous reports demonstrating the ability of human 12 and murine 18,19 mature CD45 À myeloma PCs to grow and manifest in a nonmyelomatous environment.…”
Section: Discussioncontrasting
confidence: 57%
“…To our knowledge, this is the first report demonstrating the potential of isolated primary CD138-enriched PCs to proliferate, propagate, and produce typical myeloma manifestations in vivo. These results are in contrast to recent study showing the inability of purified CD138-expressing PCs to grow in NOD/SCID mice, 8 but in accord with previous reports demonstrating the ability of human 12 and murine 18,19 mature CD45 À myeloma PCs to grow and manifest in a nonmyelomatous environment.…”
Section: Discussioncontrasting
confidence: 57%
“…3,8,18 During normal development, the marrow is populated predominantly by the CD45 þ population, which represents the early stage PCs. As they mature to terminally differentiated plasma cells, the CD45 expression is gradually lost.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CD45 among the PCs in the bone marrow of patients with MM is heterogeneous. 3,8 The weight of evidence suggests the presence of two populations of myeloma cells in the marrow; early PCs with CD45 expression and late PCs with dim or no expression. Important biological differences have been demonstrated between these two populations including their proliferative capability, IL-6 responsiveness and dependence, chromosomal abnormalities and angiogenic capability.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that both human 23 and murine 24,25 MM cell lines can demonstrate heterogeneous expression of several MM-related cell surface antigens. Therefore, we analyzed the expression of CD138 in 2 distinct human MM cell lines, RPMI 8226 and NCI-H929.…”
Section: Distinct Phenotypic and Functional Cell Populations Are Presmentioning
confidence: 99%